Automated Parallel and Body-Fitted Mesh Generation in Finite Element Simulation of Macromolecular Systems (Communications in Computational Physics, 2018)
Mesh generation is a bottleneck for finite element simulations ofbiomolecules. A robust and efficient approach, based on the immersed boundarymethod proposed in [8], has been developed and implemented to generate large-scalemesh body-fitted to molecular shape for general parallel finite element simulations.The molecular Gaussian surface is adopted to represent the molecular surface, andis finally approximated by piecewise planes via the tool phgSurfaceCut in PHG [43],which is improved and can reliably handle complicated molecular surfaces, throughmesh refinement steps. A coarse background mesh is imported first and then is distributedinto each process using a mesh partitioning algorithm such as space fillingcurve [5] or METIS [22]. A bisection method is used for the mesh refinements accordingto the molecular PDB or PQR file which describes the biomolecular region. Aftermesh refinements, the mesh is optionally repartitioned and redistributed for load balancing.For finite element simulations, the modification of region mark and boundarytypes is done in parallel. Our parallel mesh generation method has been successfullyapplied to a sphere cavity model, a DNA fragment, a gramicidin A channel and a hugeDengue virus system. The results of numerical experiments show good parallel efficiency. Computations of electrostatic potential and solvation energy also validate themethod. Moreover, the meshing process and adaptive finite element computation canbe integrated as one PHG project to avoid the mesh importing and exporting costs,and improve the convenience of application as well.